Suzuki Violin School Piano Part Vol. 8 - Suzuki (Zen-On Music Publisher Co, Ltd, 1974)
1. Sonata g minor - H. Eccles2. Tamborin - A.E. Gretry3. Largo - J.S. Bach4. Allegro - J.S.Bach5. Largo Espressivo - G. Pugnani6. Sonata - F.M. Veracini